PENGARUH INVESTASI SUMBER DAYA MANUSIA DAN PENDAPATAN PERKAPITA TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DI PROVINSI RIAU - Maidoni, Dede Afri; Kadir, Hainim; Indrawati, Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research intend to understand and analyzing the influence of human resources investment through the allocation of government education sector, the health sector and income per capita against the human development index (HDI) in Riau Province. This research uses secondary data from the years 2004-2013, published by the central bureau of statistics Indonesia. The analytical method used is multiple liniear regression analysis with SPSS 20. Simultaneously, this research showed that spending of government education variable, spending of government health variable and per capita income variable is jointly affect the human development index (HDI). Partialy showed that per capita income is only a significicant effect on the human development index (HDI). While the spending of government education sector variable and spending of government health sector variable doesn’t significantly influence against the human development index(HDI) in Riau Province. The amount due to the influence of three independent variables simultaneously against dependent variable is 96,9% while the remaining 3,4% is influenced by other variables which is not examined in this research.Keywords: human development index (HDI), allocation of government education sector, allocation of government health sector and per capita income.